2020
DOI: 10.47162/rjme.61.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TP53 gene and particular infrastructural alterations in invasive ductal mammary carcinoma

Abstract: This study was conducted in order to determine the mutational status of TP53 gene and to determine some particular aspects from ultrastructural level in invasive mammary ductal carcinoma. The cellular signaling pathway involving the TP53 gene acts in biological deoxyribonucleic acid (DNA) repair processes and cell cycle arrest following a signal transmitted to the p53 protein when posttranslational changes occur in the cell due to stress induced in the cell by both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Consistent with data from literature, we also demonstrated that an aberrant p53 immunoexpression has a prognostic value since its presence is associated with a worse DMFS. The mutant p53 protein acquired more functions than the “wild-type” p53 protein (normal immunoexpression) and can trigger the immune system by expressing itself on the tumor cell surface through histocompatibility complex (neoantigen) [ 22 , 43 , 44 ]. It was also demonstrated that mutation of TP 53 gene can lead to a poor reaction of CD8+ T-cells, which can affect the response to the immunotherapy [ 45 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Consistent with data from literature, we also demonstrated that an aberrant p53 immunoexpression has a prognostic value since its presence is associated with a worse DMFS. The mutant p53 protein acquired more functions than the “wild-type” p53 protein (normal immunoexpression) and can trigger the immune system by expressing itself on the tumor cell surface through histocompatibility complex (neoantigen) [ 22 , 43 , 44 ]. It was also demonstrated that mutation of TP 53 gene can lead to a poor reaction of CD8+ T-cells, which can affect the response to the immunotherapy [ 45 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Moreover, in different pathologies, TCs can be altered in their morphology and their number in surrounding stroma [19,[22][23][24]50]. In this line, Sabatelli et al (2022) [51] reported that in Ullrich congenital muscular dystrophya devastating inherited neuromuscular disorder [52] -, cluster of differentiation 34 (CD34)-positive TCs increase in their number in the interstitium of the deep fascia, Tps pass through dissoluted basal lamina and contact the sarcolemma of underlying muscle fiber aspects, which suggest a potential involvement of TCs in the pathogenesis.…”
Section: The Remarkable Feature Of Tcs Is the Variety Of Their Cell-c...mentioning
confidence: 99%
“…During regeneration of post-injured skeletal muscle, TCs may activate and regulate satellite muscle cells activity by invading satellite cell niche by their long Tps through local destructured basal lamina succeeded to contact the adjacent activated satellite cells [ 49 ]. Moreover, in different pathologies, TCs can be altered in their morphology and their number in surrounding stroma [ 19 , 22 , 23 , 24 , 50 ]. In this line, Sabatelli et al (2022) [ 51 ] reported that in Ullrich congenital muscular dystrophy – a devastating inherited neuromuscular disorder [ 52 ] –, cluster of differentiation 34 (CD34)-positive TCs increase in their number in the interstitium of the deep fascia, Tps pass through dissoluted basal lamina and contact the sarcolemma of underlying muscle fiber aspects, which suggest a potential involvement of TCs in the pathogenesis.…”
Section: Tcs Have a Particular Infrastructural Phenotype And Express ...mentioning
confidence: 99%
See 2 more Smart Citations